Keragaman Herpetofauna di Kabupaten Bantul, Daerah Istimewa Yogyakarta - Dwi Nuryan Dani; Kusmardiastuti; Susilo Irwanjasmoro; Emmanuel Glodias Boggy Sanjaya; Rury Eprilurahman (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2025)
The group of amphibians and reptiles, also known as herpetofauna, are an important parameter in maintaining the balance and sustainability of ecosystems. The decline in herpetofauna populations serves as an indicator of changes in environmental quality in a given area. Herpetofauna have specific habitats that act as indicators or early warnings of environmental changes. In addition to ecological benefits, herpetofauna are also economically beneficial. Herpetofauna have long been utilized by the Indonesian community for experimentation, research, medicine, pets, handicrafts, and as a source of animal protein. Bantul Regency has a quite complex landscape consisting of lowlands, hills, coastal areas, and karst formations. The research on herpetofauna diversity aims to determine the herpetofauna diversity in Bantul Regency. The benefit of this research is to provide information on the diversity of herpetofauna species in Bantul Regency to the community, the academic environment, and related institutions, as well as to serve as a consideration in the management of areas related to spatial planning, forest management, and biodiversity conservation. The research was conducted from October 21-26, 2024, during the transition from the dry season to the rainy season. The sampling area covers 113.48 Ha. The method used was direct encounters. (VES). The research identified 21 species of herpetofauna, consisting of 8 species of amphibians and 14 species of reptiles. The Shannon-Wiener diversity index is 1.6498, which falls into the moderate category. The evenness index is 0.5337, indicating that the evenness of herpetofauna in Bantul Regency is quite high and there is no dominance of any particular species